PENDAMPINGAN MENINGKATKAN MUTU MANAJEMEN PAUD BINAAN - Yecha Febrieanitha Putri; Indah Dwi Sartika; Fahmi Fahmi (Scientia: Jurnal Hasil Penelitian, 2021)
The research aimed to find out whether the quality of PAUD management assistance could improve. Research-based service was carried out at RA Perwanida 3 and PAUD Kaisah. This study used the Participatory Action Research (PAR) model of the Kemmis, S. & McTaggart , R. Research methodology which was carried out in a series through online material delivery assistance and direct mentoring to each PAUD unit. The implementation of the activity is carried out in 5 steps, namely diagnosis, making an action plan, taking action, evaluating and reflecting. Data analysis using data analysis quantitative data analysis and qualitative data analysis. Quantitative data analysis was obtained from the description of the value of document completeness, pre and post mentoring. While the qualitative data analysis was obtained from field notes, documentation notes and interview notes using four parts, namely data reduction, display data and conclusion data. The results of the dedication research with assistance to improve the quality of the assisted PAUD management, the average document data obtained from each of the assisted institutions has increased by 37%, which is based on 30 assessment indicators, 26 indicators have been successfully fulfilled by each of the assisted PAUD institutions so that initially the average file completeness was 49% after being given assistance to 86%.